2021
DOI: 10.1108/afr-06-2021-0073
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional lenders and access to local agricultural credit markets by beginning and female farmers

Abstract: PurposeThe purpose of this study is to evaluate if access to local branch infrastructure of the farm credit system institutions (FCS), banks and credit unions (BCU), and alternative financial services (AFS) providers is related to the use of credit from non-traditional lenders (NTLs). The focus is on beginning and women operators who are typically credit constrained and thus more likely to suffer from closures of bank branches and consolidation of traditional agricultural lenders.Design/methodology/approachInf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…For instance, Doss et al (2018) in Ethiopia found that social networks and trust played a critical role in farmers' decisions to access informal credit. Similarly, Agbola et al (2022) revealed that factors such as social capital, informal savings groups, and cultural norms significantly influenced farmers' participation in informal credit markets in Nigeria. Similarly, Alemayehu et al (2020) in Ethiopia and Murendo et al (2021) in Zimbabwe highlighted the importance of social networks and trust in facilitating farmers' participation in informal credit markets.…”
Section: Determinants Of Agricultural Credit Demand and Participation...mentioning
confidence: 99%
“…For instance, Doss et al (2018) in Ethiopia found that social networks and trust played a critical role in farmers' decisions to access informal credit. Similarly, Agbola et al (2022) revealed that factors such as social capital, informal savings groups, and cultural norms significantly influenced farmers' participation in informal credit markets in Nigeria. Similarly, Alemayehu et al (2020) in Ethiopia and Murendo et al (2021) in Zimbabwe highlighted the importance of social networks and trust in facilitating farmers' participation in informal credit markets.…”
Section: Determinants Of Agricultural Credit Demand and Participation...mentioning
confidence: 99%
“…The authors attribute this income disparity to differences in resources, experience, and commodity production choices. Nadolnyak and Hartarska (2021) analyzed the local agricultural credit market and how female farmers' access to financial services impacts their use of credit. They find that “[w]hile access to farm credit institutions is not associated with their use of loans, access to both alternative financial services and banks and credit union options inform their borrowing choices and loans from non‐traditional lenders and banks and credit unions may be substitutes but loans from non‐traditional lenders remain a smaller part of women's loan portfolios” (Nadolnyak & Hartarska, 2021, p. 14).…”
Section: Literature Review: Women Farmersmentioning
confidence: 99%
“…Nadolnyak and Hartarska (2021) analyzed the local agricultural credit market and how female farmers' access to financial services impacts their use of credit. They find that “[w]hile access to farm credit institutions is not associated with their use of loans, access to both alternative financial services and banks and credit union options inform their borrowing choices and loans from non‐traditional lenders and banks and credit unions may be substitutes but loans from non‐traditional lenders remain a smaller part of women's loan portfolios” (Nadolnyak & Hartarska, 2021, p. 14). Therefore, faced with these challenges and given their unique goals, women farmers operate smaller farms, focus on livestock and horticultural operations, and emphasize direct‐to‐consumer sales.…”
Section: Literature Review: Women Farmersmentioning
confidence: 99%
“…Nadonlyk and Hartarska (2022) also use ARMS data in their study on “Nontraditional lenders and access to local agricultural credit markets by beginning and female farmers.” They link the farms sampled in ARMS to county-level branch density of Farm Credit System, banks and credit unions and alternative financial services [3]. They then use several econometric models to regress different loan outcomes on credit access.…”
Section: Borrowersmentioning
confidence: 99%
“…3. Nadonlyk and Hartarska (2022) define alternative financial services as “AFS are financial services provided outside traditional banking institutions and proxy here for the insufficient banking services in the county […] AFS include rent-to own agreements, pawnshops, refund anticipation loans, some subprime mortgage loans, car title loans, payday loans and private moneylenders.”…”
Section: Notesmentioning
confidence: 99%